Foreign Direct Investment and Female Entrepreneurship - Fang, Sheng; Shamseldin, Heba M.M.; Xu, L. Colin (World Bank, Washington, DC, 2019)
Using World Bank Enterprise Survey data around the world, this paper examines how foreign direct investment is associated with female entrepreneurship (that is, a firm being managed and at least partly owned by women), along with other factors such as business environment and female empowerment, and their interactions with foreign direct investment. Female entrepreneurship rises with foreign direct investment inflow, lower entry barriers for women, women's better access to finance, higher female labor force participation, and women's better education. The positive association of foreign direct investment inflow and female entrepreneurship is stronger for firms in the service sectors and small firms. The horizontal competition effects of intra-industry foreign direct investment for female entrepreneurship are reduced when women face lower entry barriers for starting a business and have a higher labor force participation rate, and the effects do not depend on women's access to finance or their level of education.